Medical education advances and innovations: A silver lining during the COVID-19 pandemic - Mehta, Nishila; Sayed, Céline; Sharma, Rishi; Do, Victor (Canadian Medical Education Journal, 2020)
The COVID-19 pandemic has disrupted healthcare processes substantially including medical education, necessitating several changes along the spectrum of medical training. While this crisis presents major challenges to medical education, it is also an immense opportunity for innovation. In this commentary, Canadian medical students cast a spotlight on four domains of Canadian medical education which have seen substantial changes during the COVID-19 pandemic: medical school admissions, pre-clerkship content delivery, virtual care and telemedicine curricula, and the residency matching process. Using the 10 recommendations noted in the Association of Faculties of Medicine of Canada (AFMC) 2010 Future of Medical Education in Canada report as a guiding framework, we discuss why these changes represent key steps forward that should be preserved in medical education beyond the pandemic, and advocate for a continuous quality improvement approach to evaluate and implement these innovations.